Detection of FSH receptors in mouse and human penile tissue - Helen Zirnask; Pasi Pöllänen; Siim Suutre; Taavi Torga; Samuel Rüsse; Liis Salumäe; Andres Kotsar; Kersti Kokk (Journal of Men's Health)
Background: This study aims to investigate the expression of follicle-stimulating hormone (FSH) receptors in both mouse and human penis to explore its potential impact on penis function. Methods: We utilized immunohistochemistry to detect FSH receptors in penile and testicular tissues from 12 BALB/c mice, as well as penile tissues from three patients undergoing penectomy for squamous cell carcinoma. Results: Positive immunoreaction for FSH receptors was detected in tissue samples of all patients including sebaceous gland, epithelial layers, subepithelial fibroblasts, corpus cavernosum cells, walls of small blood vessels and plasma cells. However, species specificity was observed in the results, as positive immunoreaction was absent in the most of mouse penis tissue samples. Fibrocytes and mast cells in the mouse penis exhibited negligible positive immunoreaction. Conclusions: This study marks the first reported detection of FSH receptors in human penile tissue, highlighting a potential extragonadal role for FSH in penile function. While human tissues exhibited widespread receptor expression, mouse tissues showed minimal immunoreactivity, suggesting species-specific expression patterns. These preliminary findings indicate a possible regulatory role for FSH in human penile physiology, meriting further exploration in subsequent studies.